Is Exercise Beneficial in Patients with Low Back Pain? - A Cochrane Review Summary with Commentary - Frane Grubišić (Medical Journals Sweden, 2022)
The aim of this commentary is to discuss from a rehabilitation perspective the Cochrane Review "Exercise therapy for chronic low back pain" (1) by Hayden JA, Ellis J, Ogilvie R, Malmivaara A and van Tulder MW [1] published by Cochrane Musculoskeletal Group. This Cochrane Corner is produced in agreement with Journal of Rehabilitation Medicine by Cochrane Rehabilitation with views* of the review summary authors in the "implications for practice" section. This summary is based on a Cochrane Review previously published in the Cochrane Database of Systematic Reviews 2021, Issue 9, Art. No.:CD009790, DOI: 10.1002/14651858.CD009790.pub2 (see www.cochranelibrary.com for information). Cochrane Reviews are regularly updated as new evidence emerges and in response to feedback, and Cochrane Database of Systematic Reviews should be consulted for the most recent version of the review. * The views expressed in the summary with commentary are those of the Cochrane Corner author (different than the original Cochrane Review authors) and do not represent the Cochrane Library or Journal of Rehabilitation Medicine.